Effects of Lemuru fish oil (Sardinella sp.) on estrous response, hormonal profile and conception rates in Garut ewes - Nurlatifah, Aeni; Herdis, Herdis; Menassol, Jean-Baptiste; Khotijah, Lilis; Arifiantini, Raden Iis; ShikhMaidin, Mashitah; Astuti, Dewi Apri; Sitaresmi, Pradita Iustitia (University of Agriculture, 2024)
The aim of this study was to determine the effects of short-term feed supplementation of Lemuru fish oil on the reproductive performance of 20 primiparous Garut ewes. For this purpose, the effects of four diets were compared: a control diet (C) and three diets with various oil supplements. These diets were: 6% palm oil (P1), 3% palm oil with 3% Lemuru fish oil (P2), and 6% Lemuru fish oil (P3). Experimental ewes were subjected to estrous synchronization using two injections of PGF2α 11 days apart. The hormonal profiles and blood metabolites were monitored for animals of each group. Estrous expression was observed at mating, and embryo counts were recorded individually using trans-rectal ultrasonography 20 days after mating. Results showed that plasma concentrations of cholesterol were significantly (P<0.05) higher for P2 and P3 (44.90±10.51 and 49.81±14.37 mg/dL, respectively) than control and P1 groups. Similarly, blood estradiol concentrations were significantly higher for P3 than P1 and P2 groups before estrus, while during estrus P3 had higher blood estradiol than control group (P<0.05). All treatment diets significantly enhanced the onset of estrus in comparison with control animals (P<0.05), while receptivity was higher for P3 (21.80±2.86 times) than for control group (P<0.05). The proportion of ewes pregnant after the first estrus was the highest for P3 (100%) compared to all other diets. However, there was no effect of diets on the number of embryos. In conclusion, feed supplementation of Lemuru fish oil improves reproductive performance of ewes following natural mating by stimulating onset of estrus and increasing pregnancy rates, making Lemuru oil an attractive feed supplement.